Genetic diversity and population structure of the antimalarial plant Cryptolepis sanguinolenta in Ghana - Amissah, Jacqueline Naalamle; Hadziabdic, Denita; Boggess, Sarah L.; Trigiano, Robert N. (Frontiers in Conservation Science, 2022)
Cryptolepis sanguinolenta is an important medicinal plant used in the treatment of malaria in Ghana. Overharvesting, destruction of entire plant populations and poor seed viability have resulted in a substantial decrease in wild populations thereby threatening its long-term potential and survivability. In this study, fifteen polymorphic microsatellite loci were used to evaluate the genetic diversity and population structure of 179 C. sanguinolenta individuals among eight sub-populations in Ghana. The subpopulations were separated by a distance of 8.3 – 233.3 km. Our results indicate relatively high levels of genetic diversity (Ho= 0.41; He=0.61) and high gene flow (Nm=7.06), an indication of greater stability and adaptability within the ecosystem, limited genetic differentiation (mean FST=0.05; highest FST=0.1), which suggested insignificant differentiation among the sub-populations. The high levels of gene flow resulting from the wind-dispersed seeds may have contributed to the limited genetic differentiation among the subpopulations. The Bayesian cluster analysis revealed the presence of a population (K=2). A lack of isolation by distance (r=0.012; P=0.34) indicated an increase in the genetic similarity among the subpopulations as the geographic distance between them decreased. This study describes the genetic diversity and population structure in the current C. sanguinolenta accessions and lays a foundation for future breeding efforts. Introduction